The Role of BAN PAUD AND PNF in Improving Academic Quality - Susilo Surahman (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Accreditation is a series of activities in meeting and or maintaining the quality of education in line with the government's regulations. This research aims to explain the role of BAN PAUD and PNF in improving academic quality, especially in PAUD units. This research is a type of normative or literature research. The results showed an Accreditation Prerequisite Assessment (PPA) of PAUD Unit as one of the new regulations intended to facilitate educational institutions in the assessment process, especially accreditation. As part of the accreditation process, the Paud Unit's Visitation Assessment Instrument (IPV), as part of the accreditation processis based on performance-based assessment in measuring the level of unit achievement in knowledge, attitudes, and interests, which are tailored to theneeds of learners the community. Government regulations issued in line with the PAUD accreditation process are currently intended to make it easier for educational institutions to conduct assessments, both internally and externally.Akreditasi merupakan rangkaian kegiatan dalam memenuhi dan atau mempertahankan kualitas mutu pendidikan, sejalan dengan regulasi yang telah ditetapkan oleh Pemerintah. Penelitian ini bertujuan untuk menjelaskan peran BAN PAUD dan PNF dalam peningkatan kualitas akademik, khususnya pada satuan PAUD. Penelitian ini merupakan jenis penelitian normatif atau kepustakaan. Hasil penelitian menunjukkan bahwa terdapat Penilaian Prasyarat Akreditasi (PPA) Satuan PAUD sebagai salah satu regulasi baru yang dimaksudkan sebagai upaya mempermudah lembaga pendidikan dalam proses penilaian, khususnya akreditasi. Instrumen Penilaian Visitasi (IPV) Satuan PAUD sebagai bagian dari proses akreditasi didasarkan pada penilaian berbasis performance dalam mengukur tingkat pencapaian satuan dalam pengetahuan, sikap dan keterampilan, yang disesuaikan dengan kebutuhan peserta didik dan masyarakat. Regulasi pemerintah yang dikeluarkan sejalan dengan proses akreditasi PAUD saat ini dimaksudkan sebagai upaya mempermudah lembaga pendidikan melakukan penilaian, baik secara internal maupun eksternal.